The relationship between job satisfaction and job performance : a case study of a malaysian electronic organization - Syaidatul Akma, Bahani (2013)
The aim of this research is to study the relationship between job satisfaction and job, performance. For Job satisfactions, pay, promotion, the work itself, supervision and co- workers rotation are set as the independent variables. Then, job performance at the work is the dependent variable. Two hundred seventeen respondents from Khind’s electronic manufacturing industry were surveyed by questionnaire. The collected data was analysed by using Cronbach's alpha (reliability analysis), correlation analysis, t-test, factor analysis (KMO) and regression analysis. Results show that there are significant positive relationships between job satisfaction dimensions (pay, promotion, work itself, supervision, and co-worker) and job performance and the findings are in accordance with previous researches.